2006
DOI: 10.1002/lsm.20354
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial photodynamic therapy for lung cancer

Abstract: PDT is an effective tool for the palliation of endobronchial lung cancers which obstruct the central airways and is also effective for the treatment of central microinvasive carcinoma and carcinoma in situ of the central airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 53 publications
1
59
0
Order By: Relevance
“…In our experiments, we varied light rather than photosensitizer dose because the lack of drug-light reciprocity due to sensitizer photobleaching can cause artifacts at low photosensitizer concentrations (29) and also because clinically, a fixed dose of the photosensitizer is given, whereas the physician can alter the light dose. Because HPPH is a derivative of pyropheophorbide-a, the results for this agent, which is in promising phase II trials (30,31), are consistent with the recent report of Robey et al that pyropheophorbide-a is a substrate of ABCG2 (8). As shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In our experiments, we varied light rather than photosensitizer dose because the lack of drug-light reciprocity due to sensitizer photobleaching can cause artifacts at low photosensitizer concentrations (29) and also because clinically, a fixed dose of the photosensitizer is given, whereas the physician can alter the light dose. Because HPPH is a derivative of pyropheophorbide-a, the results for this agent, which is in promising phase II trials (30,31), are consistent with the recent report of Robey et al that pyropheophorbide-a is a substrate of ABCG2 (8). As shown in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…DNA microarray analysis indicated the absence of ATDC expression in prostate cancers on the basis of mRNA expression level (Ernst et al, 2002). So far, results of several expression analyses of TRIM29 using human normal and cancer tissues have been reported with TRIM29 being highly expressed in the lung, bladder, colorectal, ovarian, endometrial cancers and multiple myeloma (Dyrskjot et al, 2004;Glebov et al, 2006;Hawthorn et al, 2006;Loewen et al, 2006;Mutter et al, 2001;Santin et al, 2004;Zhan et al, 2002). Previous analyses also suggested that TRIM29 is involved in the response to DNA damage through p53 and functions as an oncogene that promotes tumorigenesis (Sho et al, 2011;Yuan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Simulations performed at 670 nm were chosen to correspond to the absorption of photosensitizers such as HPPH or methylene blue. HPPH has been used in the treatment of thoracic malignancies, 27,28 Barrett's esophagus, 29 and early cancers and precancers of the oral cavity. 30 Methylene blue is FDA-approved as a diagnostic dye and is the only known treatment for methemoglobinemia.…”
Section: Discussionmentioning
confidence: 99%